Knowledge of nursing students on dysthanasia - Mariana Costa Matos; Darci de Oliveira Santa Rosa; Karla Ferraz dos Anjos (Universidade Federal do Ceará, 2015)
Objective: to evaluate the knowledge of nursing students about the dysthanasia as a process of human intervention in terminally ill patients. Methods: a qualitative study with 28 nursing students from a public higher education institution. Data analysis of the interviews was through thematic content analysis. Results: it was found that most students do not understand the meaning of dysthanasia, though living with situations involving this practice in their training. Those who defined the term described it as the excessive prolongation of life or death suffered from much pain, aggressive treatment that only prolongs the process of dying. Conclusion: it was evidenced that nursing students have insufficient knowledge of the dysthanasia and it is necessary to broaden the discussion spaces during the graduate course and conduct studies on the subject relating it to the death and dying process, for the preparation of future health professionals.